Metadata extraction with cue model - Wan Isa, Wan Malini; Abdul Hamid, Jamaliah; Ibrahim, Hamidah; Abdullah, Rusli; Selamat, Mohd. Hasan; Abdullah, Muhamad Taufik; Nasharuddin, Nurul Amelina (2008)
Metadata extraction from texts is import ant since it enables search for documents based on the metadata identified.It is impossible to retrieve journal articles without the metadata of documents, which includes information such as author, title, and journal publication details.This paper proposes a new technique to extract metadata of documents, called Metadata Extraction with Cue Model, which uses combinations of a few features to extract metadata automatically from documents. Automatic metadata extraction is increasingly important in today’s influx of published material.